Impact of improved production technology of groundnut (Arachis hypogaea L.) on farm productivity and income in Western Maharashtra: IMPACT OF IMPROVED PRODUCTION TECHNOLOGY OF GROUNDNUT ON FARM PRODUCTIVITY - K G SONAWANE; V G POKHARKAR; C M GULAVE (Journal of Oilseeds Research, 2016)
Groundnut (Arachis hypogaea L.) is an important leguminous oilseed crop grown in India occupies an area of 5.49 million ha. The groundnut grown in Western Maharashtra was selected forthe studywith the objectives to study the employment, income and expenditure pattern, effects ofimproved production technology on per hectare resource use structure, costs and returns, constraints in adoption of improved technologies, input use gap and yield gap. The study was carried out in 15 tahsils, 30 groundnut growers were selected randomly i.e., 10 from each of the category of small, mediumand large size farms. Thus, in all 450 groundnut growers (150 fromeach size group) were selected. The annual average employment of groundnut sample family was found to be 409.60 days. The total employment of a female worker of sample families was 90.33 days. The average annual gross income of the sample families at the overall level was ` 5,49,380. The crop production alone accounts near about half of the annual expenditure in all adoption groups. There exists an excessive gap (from 12 to 76%) in the use of manures. The gap in seed use was 32.79 per cent. The ICBR indicates that the high adopter farmers were in profit with 2.02. It clearly indicates that the farmers should adopt the improved technologies of groundnut to the fuller extent for maximizing returns and minimizing per unit cost. The yield gap was ranged between 68 to 88 and 43 to 78 per cent, respectively. The nine independent variables have jointly explained the 45 per cent variation in output for groundnut. The variables viz., human labour, phosphorus, plant protection and number of irrigation were highly significant indicating that these are the important variables for which the output is responsive.